Coexistence of abnormal systolic motion of mitral valve in a consecutive group of 324 adult Tetralogy of Fallot patients assessed with echocardiography. Issue 2 (30th December 2016) - Agarwal, Anushree; Harris, Ian S; Mahadevan, Vaikom S; Foster, Elyse
Abstract : Background: The presence of mitral valve prolapse (MVP) in congenital heart disease (CHD) patients is not well described. Tetralogy of Fallot (TOF) is the most common cyanotic CHD associated with overall good long-term survival after palliation. Since MVP is more often identified in adults and TOF patients are now surviving longer, we thus sought to perform this cohort study with a case–control design to (1) determine the prevalence of MVP and systolic displacement of mitral leaflets (SDML) in adult TOF patients, and (2) describe their clinical and imaging characteristics. Methods: Retrospective interrogation of our echocardiography database identified 328 consecutive TOF patients ≥18 years from 1 January 2000 to 31 December 2014. All images were reviewed to identify patients with concomitant MVP (prolapse >2 mm beyond the long-axis annular plane) or SDML (<2 mm beyond the annular plane). Results: 26 (8%) TOF patients fulfilled criteria for systolic mitral valve abnormality (SMVA) (15 MVP; 11 SDML). 2 had moderate to severe mitral regurgitation requiring repair. When compared with 52 TOF patients without SMVA, those with SMVA were more likely to be females (60.7% vs 33.9%, p=0.03), less likely to have transannular patch (52% vs 97.4%, p<0.0001), had lower right ventricular ejection fraction (36.5% vs 43.8%, p=0.03) and a trend towards increased risk of atrial (44% vs 30.4%, p=0.5) and ventricular arrhythmias (32% vs 25.5%, p=0.6). On multivariate logistic regression, SMVA was independently associated with the absence of transannular patch (p=0.002) and atrial arrhythmias (p=0.04). Conclusions: In this series of adult TOF patients, we describe a novel finding of a high prevalence of systolic mitral valve abnormalities.